Job Satisfaction, Cost Management Knowledge, Budgetary Participation, and Their Impact on Performance - Farahmita, Aria (International Research Journal of Business Studies, 2016)
This research aims to investigate the influence of the manager’s level of cost management knowledge and job satisfaction on the relationship between budget participation and managerial performance. This research uses theoretical framework of individual performance who claims that individual performance is affected by three dimensions of performance which interact each other, i.e. dimensions of opportunity (participatory budget), dimensions of capacity (cost management knowledge) and the dimensions of willingness (job satisfaction). Hypotheses were tested using multivariate regression models that included interaction of three variables (3-way interaction) between budgetary participation, cost management knowledge and job satisfaction to test their effects on managerial performance. Research shows that budget participation which is given to managers with higher cost management knowledge and higher job satisfaction, had no impact to their managerial performance. Managerial performance variation can be explained by two dimensions. Based on our tests, the findings is consistent that budget participation has positive effect to managerial performance. Further test shows that managerial performance will increase when budget participation combined with high level of cost management knowledge or when budget participation combined with high job satisfaction (2 way interaction). The research also found that the combination of cost management knowledge with high job satisfaction without the opportunity to participate in the budgeting process will actually degrade the managerial performance.